Fractal features of soil texture and physical attributes in indian dark earth under different uses in western amazon - Jordão, Half Weinberg Corrêa [UNESP]; Campos, Milton César Costa; da Cunha, José Maurício; de Oliveira, Ivanildo Amorim; Silva, Laércio Santos [UNESP]; de Brito Filho, Elilson Gomes; Mantovanelli, Bruno Campos; de Freitas, Ludmila; Gomes, Romário Pimenta [UNESP] (PPUFU - Portal de Periódicos da Universidade Federal de Uberlândia, 2020)
Studying particle size distribution is important to understand soil structure and formation processes. This research aimed to assess the fractal dimension of soil texture in Indian Dark Earth (IDE) areas in southern Amazonas state under different land uses, as follows: two areas in the municipality of Apuí, one growing cocoa and the other coffee; a grassland area in the municipality of Manicoré; and a forest area in the municipality of Novo Aripuanã. A sampling grid containing 88 collection points (intersecting points on the grid) was established in each area, measuring 80 x 42 m for the cocoa and coffee-growing sites, and 80 x 56 m and 60 x 42 m for the grassland and forest areas, respectively. Soil samples were collected in soil core and as clumps at a depth of 0.0-0.20m to determine the structural physical properties and texture of the soil. The following physical attributes were assessed: texture (PSD), bulk density (BD), macroporosity (Macro), microporosity (Micro), total porosity (TP) and aggregate stability (GMD and WMD). The fractal dimension (D) of the soil texture was determined, followed by analysis of variance and comparison of the means using Tukey’s test (p≤0.05). Pearson’s correlation was applied to assess the correlation between variables. There was a significant difference between the IDEs studied, with a higher D value in the cocoa-growing area in relation to the other sites. Additionally, the larger the clay fraction, the higher the D value. Fractal dimension (D) showed a positive correlation with sand, clay, BD, Macro, GMD and WMD, and a negative correlation with silt, micro, TP. Based on the D values obtained, the ADE cultivated with cocoa showed superior quality in relation to the other areas studied.
Características fractais da textura e atributos físicos do solo em areas com terra preta de índio sob diferentes usos na amazônia ocidental
Keywords: Fractal dimension; Soil physics; Soil use